Nutritional components in instant porridge fortified with fermented lebui beans - Mushollaeni, Wahyu; Rahmawati, Atina (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Functional food refers to a food product that includes nutritional elements, supplements, or bioactive compounds designed to enhance health, boost the immune system, and aid in disease prevention. Functional food enriched with bioactive compounds, minerals, vitamins, fatty acids, dietary fiber, or probiotics. One form of functional food is healthy instant porridge. This study explores the nutritional composition of instant porridge fortified with fermented lebui beans. Lebui bean is the local name for black bean originated from West Nusa. The research used quantitative method analysis such us ANOVA with a factorial randomized block design with temperature (50oC and 60oC) and drying time (5, 6, 7, and 8 hours) as factors. The results showed that instant porridge containing fermented lebui bean with the best nutritional quality was obtained by drying at 60oC for 6 hours. The instant porridge had 19.49% protein, 1.58% lipid, 3.16% moisture, 2.44% ash, 3.29% fiber, 70.05% carbohydrate, 27.62 mgGAE/g phenolics, 98.21 mgQE/g flavonoids, and 85.23 ppm anthocyanin. This result provides insights into the potential of lebui beans as a functional food ingredient in the development of nutritious, ready-to-eat products.